Pembebasan Jerat Feminisasi Kemiskinan - Zahrawati, Fawziah (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2020)
The phenomenon of feminization of poverty is not a new issue in the context of poverty. Indonesia in history and process has never been free from these problems. Feminization of poverty is the loss of opportunities and freedom of women in determining life choices, thus rendering them unable to obtain educational facilities, basic economics, employment, security protection, and political involvement. Many economic observers at first saw this problem as something always related to economic factors alone. In fact, this happens as a result of cultural poverty and structural poverty which ultimately limits women from accessing existing facilities and resources. Even though various legal foundations have been born to improve gender equality in order to overcome the feminization of poverty, the problem has not yet been solved, due to the community's values and mentality that are still gender biased. Therefore, the effort that must be taken to free the snares of feminization of poverty is to change the values in society and change the structure to be more open to women by providing non-discriminatory education and employment.